The Effect of Anti Masquito Electric Gas that Consist Allethrin That Influence The Weight and Colour of Rats Liver - nurmawanti nurmawanti; Ayly Soekanto (Research and Community Service Department (LPPM) Universitas Wijaya Kusuma Surabaya, 2017)
The aim of this research is to know the influence of anti mosquito electric gas that consisted Allethrin to the weight and colour of the rats liver. This research used an experimental method with the post test only  control group design.  The subject of this research is male rats weight of 150 grams each and total there was 24 rats that were divided to 4 groups. The first one, the  control groups (PO) was not given any of the gas, the second one, group 1 (P1) was given the gas for 4 hours everday, the third one, group  2 (P2), was given for 6 hours and last, group 3  (P3) was given 8 hours everyday. After later, on  30 Th day, the rats were terminated and being put in a surgery to remove their liver. This data was analyzed using SPPS for windows version 16. To see the differences in weight between the groups, it was analyzed using anova, and  to obtain the discoloration of the rats liver was analyzed using Kruskal Wallis Test. From the statistic tests, it show that there is significant difference in weight and color of liver in the group that α ≤ 0,05. According Anova Test, it shows that there is a significant difference α = 0,034 and from Kruskal Wallis test α = 0,013. In the conclusion anti mosquito electric gas that consist Allethrin affects the weight and the color of rats liver.